How 30 great ads were made : from idea to campaign - Williams, Eliza (Laurence King, 2012)
"This book takes readers behind the scenes in the world of advertising. It looks at key advertising campaigns from the last ten years, examining how they were developed. Technical information on how the ads were created is accompanied by anecdotes from the creatives, directors, and clients, with accounts of how the ads were made and the problems encountered along the way ... As well as offering an insight into the working practices within advertising, this book also demonstrates how the industry is currently experiencing a period of rapid change, and shows the different skills that are now required to work in advertising."